2013
DOI: 10.1002/mabi.201200391
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Native Extracellular Matrix with Phytic Acid‐Crosslinked Protein Nanofibers for Cardiac Tissue Engineering

Abstract: A functional scaffold fabricated is developed from natural polymers, favoring regeneration of the ischemic myocardium. Hemoglobin/gelatin/fibrinogen (Hb/gel/fib) nanofibers are fabricated by electrospinning and are characterized for morphology, scaffold composition, functional groups and hydrophilicity. It is hypothesized that ex vivo pretreatment of mesenchymal stem cells (MSCs) using 5-azacytidine and such a functional nanofibrous construct having a high oxygen-carrying potential could lead to enhanced cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 21 publications
3
39
0
Order By: Relevance
“…These nanofibers, cross-linked with phytic acid, hold promise to be an effective therapeutic agent for myocardial regeneration. 75 Biomaterials made of poly(glycerol sebacate) (PGS) core polymer and gelatin shell polymers have good cell adhesion, proliferation, and cytocompatibility properties. 76 Ravichandran et al have observed that the transplantation of the cells -along with the short nanofibers of PGS into the infarcted myocardium -results in an enhanced retention of the cells and increased expression of cardiac proteins like troponin, actinin, and connexin 43, compared with the standard cell injection system.…”
Section: Myocardial Regenerationmentioning
confidence: 99%
“…These nanofibers, cross-linked with phytic acid, hold promise to be an effective therapeutic agent for myocardial regeneration. 75 Biomaterials made of poly(glycerol sebacate) (PGS) core polymer and gelatin shell polymers have good cell adhesion, proliferation, and cytocompatibility properties. 76 Ravichandran et al have observed that the transplantation of the cells -along with the short nanofibers of PGS into the infarcted myocardium -results in an enhanced retention of the cells and increased expression of cardiac proteins like troponin, actinin, and connexin 43, compared with the standard cell injection system.…”
Section: Myocardial Regenerationmentioning
confidence: 99%
“…1b and 1c) 23,28 and has a cross-linking effect on protein nanofibers. 27 The knowledge about IP6 and its use in adhesive dentistry are limited. Recently, it was reported that IP6 has the potential to be an effective etchant, which demonstrated good dentine bonding and minimal cytotoxicity to pulpal-like cells, when compared with PA. 29 However, the mechanism behind the high bond strength of resin adhesive to IP6-etched dentine was not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Scaffolds for corneal tissue engineering should support cell survival and promote cell differentiation toward the corneal phenotype, which can be achieved by electrospun scaffolds due their bio-mimicking nanofibrous structure and excellent biocompatibility [52,81]. …”
Section: Applications Of Electrospun Scaffolds For Corneal Tissue mentioning
confidence: 99%